PENETUAN ALE DAN AE LARVA LEPIDIOTA STIGMA F PADA TANAMAN TEBU - Alimin, Edhi Martono, dan Witjaksono (Jurnal Teknosains, 2014)
This research was conducted to determine the value of Economic Injury Level (EIL) and Economic Threshold (ET) for the larvae of Lepidiota stigma instar 1, 2 and 3 in three different locations. The amount of larvae population and plant per m2 in the field, and the weight proportion of the vanished root or to-be-eaten by a larva were needed to determine the loss of result per m2 data on the maximum harvest outcome and the harvest outcome in the field per m2. The highest proportion value of the outcome loss per m2 based on the Walker Model, which has been modified on biological control with Nematode Entomo Patogen (NEP) Steinernema spp. combined with light trap, was in Tempel Sari, i.e. larvae instar 1 (0.0108), instar 2 (0.0174), and instar 3 (0.0221). The lowest value was in Grenjeng, i.e. larvae instar 1 (0.0048), instar 2 (0.0078), and instar 3 (0.0099). There were significant differences among the three instars, where the consumption greediness of instar 3 is higher than instar 1 and 2, so the proportion value of the outcome loss per m2 of larvae instar 3 in the respective locations was higher than that of the two other instars. Determination of EIL value based on the Bode & Calvin Models gave the highest EIL value in Grenjengwith larvae instar 1 in the amount of 15.50 with ET value 12.40, instar 2 in the amount of 9.59 with ET value 7.67, and instar 3 in the amount of 7.54 with ET value 6.03. On the other hand, the lowest EIL value was found in Tempel Sari, with larvae instar 1 in the amount of 6.97 with ET value 5.58, instar 2 in the amount of 4.31 with ET value 3.45, and instar 3 in the amount of 3.39 with ET value 2.71.